دراسة أسباب الرضوض العينية في الفئة العمرية 20 – 60 سنة - تعتاع, عبد القادر; رجب, محمود; معلا, سميح (Latakia University Journal -Medical Sciences Series, 2019)
هدفت هذه الدراسة تحري الأسباب وعوامل الخطر المتعلقة بالأذيات العينية بغية تحديد النصائح الوقائية الأمثل لإنقاص الحدوث. شملت هذه الدراسة 200 مريض. صنفت مادة البحث وفق تنميط التعديل السريري الوارد في المراجعة التاسعة للتصنيف العالمي للأمراض. كانت عوامل الخطر الرئيسة: الذكورة 86.5 %, الفئة العمرية (20 - <30 سنة) 45.5 %, مكان العمل 55 %. نسبة الوقاية كانت 4.5 %, 77 % من المرضى راجعوا في يوم الإصابة ذاته. مصدر الإصابة الرئيس كان الجسم الأجنبي الدقيق 43.5 %, نمط الإصابة الرئيس كان الجسم الأجنبي السطحي (التعديل السريري الوارد في المراجعة التاسعة للتصنيف العالمي للأمراض: رقم 930) بنسبة 38 %. ينبغي أخذ هذه النتائج بعين الاعتبار عند تحديد الإجراءات الوقائية العينية. The objective of this study was to investigate the causes and risk factors of ocular trauma in order to identify the best preventive advice to reduce its incidence. This study included a total of 200 patients. Subjects were identified by the International Classification of Diseases, 9th edition, Clinical Modification (ICD-9-CM) codes. The main risk factors were: Masculinity 86.5%, age group (20-<30 years) 45.5%, and workplace 55%. Prevention rate was 4.5%, 77% of patients reported on the same day of injury. The main source of injury was the minute foreign body 43.5%; the main type of injury was superficial foreign body on eye (ICD-9-CM: n.930) 38%. These results should be taken into account when identifying ocular preventive measures.